Characterization of a hyperthermophilic sulphur-oxidizing biofilm produced by archaea isolated from a hot spring - Emky Valdebenito-Rolack; Nathaly Ruiz-Tagle; Leslie Abarzúa; Germán Aroca; Homero Urrutia (Electronic Journal of Biotechnology, 2017)
Background: Sulphur-oxidizing microorganisms are widely used in the biofiltration of total reduced sulphur compounds (odorous and neurotoxic) produced by industries such as the cellulose and petrochemical industries, which include high-temperature process steps. Some hyperthermophilic microorganisms have the capability to oxidize these compounds at high temperatures (>60°C), and archaea of this group, for example, Sulfolobus metallicus, are commonly used in biofiltration technology. Results: In this study, a hyperthermophilic sulphur-oxidizing strain of archaea was isolated from a hot spring (Chillán, Chile) and designated as M1. It was identified as archaea of the genus Sulfolobus (99% homology with S. solfataricus 16S rDNA). Biofilms of this culture grown on polyethylene rings showed an elemental sulphur oxidation rate of 95.15 ± 15.39 mg S l-1 d-1, higher than the rate exhibited by the biofilm of the sulphur-oxidizing archaea S. metallicus (56.8 ± 10.91 mg l-1 d-1). Conclusions: The results suggest that the culture M1 is useful for the biofiltration of total reduced sulphur gases at high temperatures and for other biotechnological applications.